Sistema Integrado de Gestión Administrativa (SIGA) y procesos logísticos en la UGEL Palpa 2021 - Macedo Diaz, Paholo Arturo (2022)
The objective of this research was to determine the relationship between the Integrated Administrative Management System (SIGA) and the logistics process at UGEL Palpa 2021, being an applied research with a non-experimental design, which was made up of 16 workers from said institution, the survey and questionnaire were used as a technique for collecting information, concluding that the SIGA in UGEL Palpa 2021 is regular, because the data entered for registration and evaluation sometimes shows precisely what type of process The selection process must also be followed, sometimes it is duly reconciled with the accounting office, and finally, that petty cash sometimes allows it to adapt according to its institutional directive. Likewise, the logistics process is classified as regular, because it never receives and thoroughly evaluates the offers of the suppliers, as well as sometimes verifying and controlling each of the goods to specify that it is in good condition and of quality, in Exchange almost always carries out the conditioning of materials for the respective delivery to the applicant, in addition they always use the physical inventory necessary to register the goods. In general, it is established that the relationship between (SIGA) and logistics processes in the UGEL Palpa is significant positive and considerable, since the correlation statistic r resulted with a significance of 0.000 and a coefficient of 0.904.